Focal myositis presenting as pseudothrombophlebitis of the arm. Issue 4 (April 2016) - Roverano, Susana; Ortiz, Alberto; Paira, Sergio
Abstract We described a 21-year-old woman with a diagnosis of Sjögren syndrome that came for consultation with a localized mass over her left arm of fast growth. Lab results were normal; a Doppler ultrasound showed the presence of partial thrombosis in the left axillary vein; a magnetic resonance imaging showed edema on the biceps muscle and the biopsy of the mass disclosed the presence of severe lymphocyte infiltrate within the connective tissue and scarce muscle fibers. Immunostaining showed positive results for antígeno comun leucocitario in spanish (leukocyte common antigen) (ACL) and CD3. Those results are consistent with the diagnosis of focal myositis. The patient was treated with low doses of prednisone and methotrexate, with good response.